Rare presentation of penile cancer: a case report - Deo, Arpit; Borkar, Mrinalini; Sagrule, Dhiraj; Gadade, Gopal; Borse, Shilpa (International Surgery Journal, 2023)
Penile cancer is rare. Squamous cell cancer usually starts on glans or coronal sulcus as a nodule, foul smelly ulcer or cauliflower like mass, which invades corpora cavernosa as it progresses sparing the urethra until late in the course of the disease.We report a case of 32-year-old male with squamous cell carcinoma of penis in the form of ulcer involving shaft of penis at the base with surrounding inguinoscrotal region managed with en-mass wide local excision of the malignant ulcer taking 1 cm margin from all sides with total penectomy with partial left scrotal skin excision with left orchidectomy with perineal urethrostomy with local scrotal advancement flap reconstruction with bilateral superficial inguinal lymphnode biopsy. Post op period was satisfactory. At discharge, flap was healthy with well-functioning perineal urethrostomy. Patienthad received 6 cycles of adjuvant chemotherapy.Ca penis can be present in any rare form and hence early diagnosis and timely management is the key.